Analisis Kompetensi Guru Berbasis Komunitas Belajar dan Strategi Optimalisasi Kominitas Belajar di Sekolah Dasar Kabupaten Aceh Tamiang - Rustini Rustini; Rahmi Novalita; Yulia Santi (Jurnal Ilmiah Global Education, 2026)
This study aims to analyze teacher competencies based on learning communities and formulate strategies to optimize learning communities in elementary schools in Aceh Tamiang Regency. Teachers, as the main actors in the educational process, are required to continuously develop pedagogical, professional, social, and personality competencies. One approach considered effective in developing these competencies is through collaborative, reflective, and contextual teacher learning communities. This study used a qualitative approach with descriptive methods. The research subjects included elementary school teachers involved in the learning communities, school principals, and education supervisors. Data collection techniques were carried out through in-depth interviews, observation, and documentation studies. Data analysis was carried out interactively through the stages of data reduction, data presentation, and drawing conclusions. The results show that teacher learning communities in Aceh Tamiang Regency have served as a space for sharing good practices, discussing learning issues, and strengthening understanding of the curriculum and innovative learning strategies. However, its implementation still faces various obstacles, such as time constraints, variations in teacher participation, and suboptimal school managerial support. Therefore, strategies are needed to optimize learning communities through strengthening principal leadership, structured scheduling, facilitation based on teacher needs, and the use of digital technology as a collaboration medium. This research is expected to provide theoretical and practical contributions in developing teacher competencies and become a reference for educational stakeholders in strengthening learning communities in elementary schools.